Air management techniques in dental office in post COVID era: A Literature Review - Rathi, Nilesh; Deulkar, Pranjali Vilas; Mehta, Jayati; Baliga, Sudhindra; Thosar, Nilima (Brazilian Dental Science, 2022)
The neoteric coronavirus outburst has jeopardised the health care system globally. As a result, practising dentistry has severe constraints due to production of aerosols and splatter in a large quantity. Air management gains foremost importance in reducing the transmission of SARS-COV-2 in a dental operatory. A variety of air filtration techniques have been put forth to optimize the air quality by removing the pollutants and pathogens. Amidst the blowing wave of information accessible online and on social media, it is puzzling to identify dependable research data and guidance to equip the operatory to minimize the risk of disease by aerosol, droplet and contact transmission. This paper presents comprehensive review on the different air purification technologies, their mechanism and utility in reducing viral load with the aim of providing information in regards to setting up a dental operatory with reduced risk of disease transmission in the post COVID-19 era. KEYWORDS COVID 19; Air management; HEPA filter; Air purifiers.